PENDAMPINGAN IMPLEMENTASI SISTEM INFORMASI AKUNTANSI BERBASIS KOMPUTER DAN WEB UNTUK MENINGKATKAN PROFESIONALISME PENGELOLAAN USAHA PADA KSPPS AT-TAUFIQ MITRA UMAT DESA KOTAYASA KECAMATAN SUMBANG KABUPATEN BANYUMAS - Eko Suyono; Oman Rusmana; Arintoko Arintoko (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2022)
Weaknesses still felt by microfinance institutions include the unclear organizational structure and division of work, the absence of recording and reporting of financial transactions, and the imperfect manual, computer-based, and web-based accounting information system (AIS). This PKM will be hosted at the At-Taufiq Mitra Ummah of the Sharia Savings and Loans Cooperative (KSPPS) in Kotayasa Village, District of Sumbang. The objective of this PKM is to build a manual, computerized, and web-based accounting information system for partner microfinance institutions. This PKM is scheduled for 10 months in 2022 which is ended in November 2022 so that the objective can be met. The outcomes of the accounting information system model from the research is implemented in the form of a manual-based and computer-based accounting system in this 8 months PKM project. In 2022, assistance is provided for the implementation of a computerized accounting system and the implementation of a web-based accounting information system.